Quality of life in children with epilepsy - Nikolić Dimitrije M.; Željka Rogač (Scripta Medica, 2019)
Children with epilepsy are a particularly sensitive part of population and require continuous monitoring by neuro-paediatricians, so that any behavioural and functional changes that occur during mental maturation from the side effects of the therapy, but also the consequences of the disease itself, could be timely noticed. The aim of this paper is precisely to point out the potential difference in the quality of life of children with epilepsy, through the synthesis of relevant literature, in order to alert the local professional public about the need for mutual cooperation with neuro-paediatricians, psychologists, child psychiatrists, but also social workers and teachers at school.